Ethnozoology among the Berbers: pre-Islamic practices survive in the Rif (northwestern Africa) - Aymane Budjaj; Guillermo Benítez; Juan Manuel Pleguezuelos (BMC, 2021)
Abstract Background Ethnozoological knowledge is less documented than ethnobotanical. With this field study, we aim to record and analyze the Riffian Berber knowledge about the use of animals in traditional human and veterinary medicine. Our research question is what is their knowledge of ethnozoological practices? Methods We performed semi-structured interviews with local inhabitants in Riffian vernacular language. The reliability of the sampling effort was assessed by a rarefaction curve. Data were compared with previous studies in order to determine the geographical and historical extensions of described uses and possible conservation implications for the species used. Results We obtained information regarding 107 ethnozoological uses based on 197 use reports. Among the 31 species used, mammals were most frequently cited. Diseases related to the traditional medicinal system were most frequently treated with these resources, as well as those of the respiratory, digestive, and musculoskeletal systems. Thirty percent of uses are associated with magico-religious practices. Only three of the species used are threatened at the global level, two of them extinct in the study area, indicating low potential damage to regional biodiversity from current practices utilizing native animals. Within modern Morocco, Riffians have continued practicing ethnozoological uses anathema to Islam, like the consumption of animals considered impure (dogs, jackals, wild boars, and hyenas). Conclusions The use of primarily mammalian species and of many animal body parts is likely related to the Berber belief in homology between the area of the human body in which the ailment occurs and the corresponding animal body part. These findings unveil the nature of ethnozoological practices, highly linked to folklore and culture-bound conditions, and lacking in the Western empirical rationale for nearly one third of reported uses. The consumption of animals considered impure according to Islam was probably initiated before the conquering of the Maghreb by Arabs in the seventh century and was maintained through the secular isolation of Riffians in mountain areas. This can reflect traditional healing habits being maintained over thousands of years.